Modeling reverse auction-based subsidies and stormwater fee policies for Low Impact Development (LID) adoption: a system dynamics analysis. (April 2022) - Wilkerson, Brooke; Romanenko, Eduard; Barton, David N.
Highlights: A system dynamics model of reverse auction and stormwater fee impacts on LID adoption was built Reverse auction-based subsidies are effective but may require high, long-term subsidies Stormwater fees can stimulate LID adoption but are less targeted LID adoption due to stormwater fees is less sensitive to LID performance Lower reverse auction-based subsidies funded by a stormwater fee can outperform higher subsidies Abstract: Many urban areas around the world are facing increasing pressure on stormwater management systems due to urbanization and extreme weather events caused by climate change. Low impact development (LID), including blue-green infrastructure such as rain gardens, has become an attractive addition to traditional gray infrastructure for managing stormwater. Municipalities have a limited suite of policy instruments for incentivizing installation of LID on private property. We built a system dynamics model of integrated socio-economic and hydrologic systems in Oslo, Norway to illustrate implementation of two economic incentive mechanisms: subsidies based on reverse auctions and stormwater fees. We find that policy effectiveness depends on 1) communicating realistic expectations of LID performance to landowners and 2) municipal subsidies to reach landowners without intrinsic interests in LID. Under certain conditions, lower municipal economic incentives can outperform higher economic incentives and lead to sustained long-term adoption of LID on private property.